2008
DOI: 10.1111/j.1551-8248.2008.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

1
Gender, Households, and Society: An Introduction

Abstract: A critical strength of the discipline of archaeology is that its access to the material record of human history extends well beyond the written record and includes societies and cultures unaffected by Western colonialism and capitalist penetration. Bringing to light the social relations of earlier time periods, archaeology plays a critical role in documenting the full range of human variation, a role that cannot be filled by ethnography, history, or ethnohistory with their shorter temporal spans. By questionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…It is standard fare to look at gender in studies that involve preparing and cooking food. This is because of assumptions about women's work, material culture, and spaces stereotypically associated with women, and the uncritical use of ethnographies or ethnohistoric sources that depict women doing the work of food preparation and cooking (see Brumfiel and Robin 2008;Gifford-Gonzalez 2008). On the one hand, this has been an important way to bring women into discussions about past practices, discussions that women were largely absent from for a long time.…”
Section: Gendermentioning
confidence: 99%
“…It is standard fare to look at gender in studies that involve preparing and cooking food. This is because of assumptions about women's work, material culture, and spaces stereotypically associated with women, and the uncritical use of ethnographies or ethnohistoric sources that depict women doing the work of food preparation and cooking (see Brumfiel and Robin 2008;Gifford-Gonzalez 2008). On the one hand, this has been an important way to bring women into discussions about past practices, discussions that women were largely absent from for a long time.…”
Section: Gendermentioning
confidence: 99%
“…Moving away from hierarchical trajectories and fixed biological starting points, research has trended toward approaches that examine the intersection of sex and gender with other aspects of social identity (Bolger 2013b: 10-11; see Sterling 2015)-such as age, status, class, and race-prompting more nuanced insights into the organization of labor, mortuary analysis, and the body. Problematizing the androcentric narratives of man the toolmaker (Bird 1993;Gero 1991;Owen 2005: 37-39;Sassaman 1998), man the hunter (Doucette 2001;Brumbach2006a, b, 2009), and man the farmer (Robin 2002(Robin , 2006Watson and Kennedy 1991), various studies of the division of labor have demonstrated that task division does not inevitably align with sex or gender, potentially exhibiting complementary, non-dichotomous, fluid, or intersectional arrangements (Brumfiel and Robin 2008;Cobb 2005;Crass 2001: 109;Geller2008: 122-124, 2009aGero and Scattolin 2002;Hendon 2002;Hollimon 2000;Brumbach 2006a, b, 2009;Joyce 1992;Levy 2006;Preston-Werner 2008;Rotman 2006;Stockett 2005). Rather than hierarchizing contexts of action and domains of inquiry according to value-laden assumptions about gender, researchers are placing greater emphasis on how such spheres intersect in multidimensional and multiscalar ways (Cobb and Croucher 2016;Ferrer 2016;Spencer-Wood 2013).…”
Section: Destabilizing the Binary Binds: Approaches To Differencementioning
confidence: 99%
“…First, it obscures internal household dynamics by presupposing that households are loci of uncontested cooperation and sharing, that the labor invested by household members in various acts of production and consumption is seamlessly coordinated, and that these units are void of tension, disagreement, or competition. The ethnographic literature clearly demonstrates that households are not necessarily harmonious units acting as unified decision‐making entities; rather they are often domains of disagreement and inequality whose members may work independently, negotiate issues of production and consumption, or command/coerce/exploit the labor of some household members for the benefit of others (e.g., Brumfiel and Robin ; Dwyer and Bruce ; Hartmann )…”
Section: Investigating Household Activitiesmentioning
confidence: 99%